ANALISIS TERHADAP PENTINGNYA PEMBELAJARAN SENI (RUPA) DI TINGKAT PENDIDIKAN DASAR - Hayati, Sri Nur (Universitas Negeri Semarang, 2010)
Art education in pre-school and primary education is not intended for childrento be excellent in performing arts, or be a champion in the art of dance, music, literaryarts, visual arts and so on. It is clear that art education in elementary school level is notsolely aimed at producing artists. The important thing is to make children sensitive todistinguish beauty and badness, honesty and falsehood in accordance with the truth. Infact, art education (especially visual arts) in the level of primary education has not hadadequate position or portion when it is compared to other subjects. It can be seen in thepractice of learning that has not been in accordance with the substance of the true artseducation, e.g. teaching and learning strategies, availability of facilities, studentmotivation, time allocation stated in the curriculum, evaluation systems, and humanresources. Based on the results of that analysis and the important role of arts learningat primary school level, it is necessary to consider and seek breakthrough which givesthe subject of art the same position and portion as any other subjects. Moreover, it isnecessary to realize that learning arts in primary education can give positive effects tothe holistic increase of childrens ability: cognitive, affective and psychomotor.Kata kunci: analisis, pembelajaran seni rupa, pendidikan dasar